XУДОЖНЯ КУЛЬТУРА ЯК КОМПОНЕНТ КОМУНІКАТИВНОЇ КУЛЬТУРИ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ (Педагогіка вищої та середньої школи, 2007)
In the article is considered the problem of forming the communicative culture of future teachers of music by means of art culture.